Percutaneous Treatment of Vertebral Fractures - Muto, Mario; Giurazza, Francesco; Guarnieri, Gianluigi; Miele, Vittorio; Marcia, Stefano; Masala, Salvatore; Guglielmi, Giuseppe (Seminars in Musculoskeletal Radiology, 2017)
The thoracolumbar junction and lumbosacral segment are the portions of the spinal column most prone to acute traumatic fractures. Multiple classifications and injury severity score systems have been published to standardize the management of patients, establishing stable/unstable and surgical/nonsurgical fractures. In the past, patients could be treated only by surgical stabilization or conservative methods. The latter implied bed rest, long immobilization periods, prolonged drugs therapies, and, at worst, the evolution of kyphosis. Percutaneous mini-invasive treatments have been developed to improve the quality of life of patients affected by stable fractures, by rapidly recovering mobility and preventing deformity of the spinal column. These approaches, based on assisted techniques, imply the placement of different types of expandable bone implant systems. We discuss the treatment of vertebral fractures, focusing on percutaneous procedures and analyzing indications, contraindications, and outcomes of patients affected by vertebral nonosteoporotic/nonneoplastic but traumatic fractures.
Keywords: trauma; vertebral fracture; percutaneous; assisted techniques; bone implant systems